2012
DOI: 10.1002/lary.23687
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating the golden anniversary of anterior skull base surgery: Reflections on the Past 50 Years and Its Historical Evolution

Abstract: With its inception nearly half a century ago through the pioneering work of Dandy, McLean, and Smith, anterior skull base (ASB) surgery is a relatively young discipline. It became a distinct entity in 1963 when Ketcham popularized the combined transcranial transfacial approach for en bloc resection of tumors of the paranasal sinuses extending into the anterior cranial fossa. However, because these procedures resulted in major morbidities and mortalities, alternative modes of treatment were sought. Since the 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 120 publications
0
28
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Although highly effective, these procedures often result in large SB defects that can lead to high-flow cerebrospinal fluid (CSF) leaks. These defects typically necessitate meticulous multilayer reconstruction to prevent postoperative failure.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Although highly effective, these procedures often result in large SB defects that can lead to high-flow cerebrospinal fluid (CSF) leaks. These defects typically necessitate meticulous multilayer reconstruction to prevent postoperative failure.…”
mentioning
confidence: 99%
“…CCDs are solid-state devices, usually a silicon chip that transforms optical data and light signal into electrical impulses and digital data. They are equipped with miniature cameras and can be attached to the endoscope and can be fully sterilized (36,39). The addition of CCDs improved image quality on high-resolution screens, transmission of images, and the miniaturization of the endoscopic system.…”
Section: Bell Laboratories and Charged-couple Devicesmentioning
confidence: 99%
“…Endonasal endoscopic surgery, also named minimally invasive endoscopic resection (MIER), has been used to manage sinonasal malignancy (SNM) since the 1990s 1–3. Over the past 2 decades, although MIER has become an increasingly practiced procedure, the role of endoscopic surgery in the treatment of SNM remains undetermined 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 2 decades, although MIER has become an increasingly practiced procedure, the role of endoscopic surgery in the treatment of SNM remains undetermined 4,5. Clinical studies have reported that MIER offers an equivalent benefit in terms of patients’ survival compared to anterior craniofacial resection (ACFR), improves patients’ quality of life, and decreases postoperative morbidity in carefully selected patients 3,58. However, the late presentation of SNM and its juxtaposition to important anatomical structures such as eyes and brain pose a challenge to surgical management: what should be the proper extent of resection?…”
Section: Introductionmentioning
confidence: 99%